ITO/SiOx/Si optical sensor with internal gain - Fernandes, Miguel (2012)
A visible/near-infrared optical sensor based on an ITO/SiOx/n-Si structure with internal gain is presented. This surface-barrier structure was fabricated by a low-temperature processing technique. The interface properties and carder transport were investigated from dark current-voltage and capacitance-voltage characteristics. Examination of the multiplication properties was performed under different light excitation and reverse bias conditions. The spectral and pulse response characteristics are analysed. The current amplification mechanism is interpreted by the control of electron current by the space charge of photogenerated holes near the SiOx/Si interface. The optical sensor output characteristics and some possible device applications are presented.